An investigation of affective theory of mind ability and its relation to neuropsychological functions in Alzheimer's disease. Issue 3 (25th March 2020) - Yildirim, Elif; Soncu Buyukiscan, Ezgi; Demirtas‐Tatlidede, Aslı; Bilgiç, Başar; Gurvit, Hakan
Abstract : Although cognitive theory of mind (ToM) has been largely studied within neurodegenerative disorders including Alzheimer's disease (AD), studies focusing on affective ToM are relatively limited, yielding inconsistent findings. The current study aimed at investigating affective ToM abilities within different stages of AD (mild AD dementia [ADD], mild cognitive impairment [MCI], and subjective cognitive impairment [SCI]), together with its relationship with neuropsychological functioning. Eighty‐one participants were tested with two different ToM tasks (Faux Pas Recognition Test [FPR] and Reading Mind in the Eyes Test [RMET]) and tests of attention, executive functions, episodic memory, and facial recognition. Our results showed two different affective ToM profiles in AD continuum: while ADD group performed poorly on both tasks of ToM, MCI group displayed deteriorated performance on RMET but not on FPR. In addition, ToM performance was significantly related to episodic memory and verbal fluency within the overall sample. These findings suggest that impairment in the decoding process of emotional cues could begin even in the prodromal stage of AD. In contrast, the reasoning process of emotional information, as measured with FPR, could be preserved until the dementia stage. Moreover, the relation of affective ToM with amnestic functions and verbal abilities could provide evidence of a domain‐general ToM impairment in AD.